2020
DOI: 10.1186/s12974-020-01751-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products induce microglia-mediated neuroinflammation via MAPKs-NF-κB signaling pathway and pyroptosis after secondary spinal cord injury

Abstract: Background: Inflammatory response mediated by oxidative stress is considered as an important pathogenesis of spinal cord injury (SCI). Advanced oxidation protein products (AOPPs) are novel markers of oxidative stress and their role in inflammatory response after SCI remained unclear. This study aimed to investigate the role of AOPPs in SCI pathogenesis and explore the possible underlying mechanisms. Methods: A C5 hemi-contusion injury was induced in Sprague-Dawley rats to confirm the involvement of AOPPs after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(146 citation statements)
references
References 52 publications
2
144
0
Order By: Relevance
“…Attenuating fluoride-induced oxidative stress in BV-2 microglia with the antioxidant, melatonin, results in reduced JNK activation [ 154 ]. Moreover, BV-2 microglia treated with advanced oxidation protein products, a hallmark of oxidative stress, displayed increased NOX4 expression and elevated ROS, along with p38 MAPK and JNK activation [ 155 ]. ROS from NOX4 also contribute to activation of the NLRP3 inflammasome, a driver of both amyloid-β [ 156 ] and tau [ 23 ] pathology.…”
Section: Ros Are Secondary Messengers Activating Pro-inflammatory mentioning
confidence: 99%
See 2 more Smart Citations
“…Attenuating fluoride-induced oxidative stress in BV-2 microglia with the antioxidant, melatonin, results in reduced JNK activation [ 154 ]. Moreover, BV-2 microglia treated with advanced oxidation protein products, a hallmark of oxidative stress, displayed increased NOX4 expression and elevated ROS, along with p38 MAPK and JNK activation [ 155 ]. ROS from NOX4 also contribute to activation of the NLRP3 inflammasome, a driver of both amyloid-β [ 156 ] and tau [ 23 ] pathology.…”
Section: Ros Are Secondary Messengers Activating Pro-inflammatory mentioning
confidence: 99%
“…ROS from NOX4 also contribute to activation of the NLRP3 inflammasome, a driver of both amyloid-β [ 156 ] and tau [ 23 ] pathology. Knockdown of NOX4 by RNAi reduced NLRP3 activation, suggesting a potential target to reduce NLRP3-stimulated pathology in neurodegenerative disease [ 155 ]. In a model of spinal cord injury, apocynin, a NOX-inhibitor (see above), reduced activation of p38 MAPK and JNK and expression of TNFα and IL1β [ 155 ].…”
Section: Ros Are Secondary Messengers Activating Pro-inflammatory mentioning
confidence: 99%
See 1 more Smart Citation
“…The histopathological results of this study showed that the brain tissue of mice in the JEV group and the JEV + Rapa group had obvious vascular in ammation and late glial cell proliferation, while the mice in the JEV + Wort group and the JEV + CQ group had slight vascular in ammatory response and obvious glial cell proliferation, other groups of mice showed normal. JEV infection leads to excessive microglia activation and the subsequent release of numerous pro-in ammatory cytokines, resulting in an in ammatory storm [27][28]. In order to attempt to further con rm that autophagy inhibitors can alleviate the vascular in ammatory responses of brain tissues in JEV-challenged mice, we observed that IL-6, IL-1β, and TNF-α were signi cantly downregulated in the brain tissues of JEV-challenged mice treated with autophagy inhibitors compared with those of the JEV and JEV + Rapa groups.…”
Section: Discussionmentioning
confidence: 99%
“…JE is an in ammatory disease of the central nervous system. JEV infection can cause excessive activation of microglia in the brain and, in turn, release of a large number of pro-in ammatory cytokines such as IL-6, TNF-α, and RANTES, which promote the migration and penetration of numerous white blood cells into the brain, resulting in an in ammatory storm that causes severe damage to the brain tissues [27][28].…”
Section: Introductionmentioning
confidence: 99%